Artificial neural networks in civil and structural engineering: Ten years of research in Poland - Waszczyszyn, Zenon (Computer Assisted Methods in Engineering and Science, 2022)
This state-of-the-art paper reports the last ten year results, obtained by an informal research group completed of participants of some Polish universities at the Institute of Computer Methods in Civil Engineering (now Institute of Computational Civil Engineering) of the Cracow University of Technology, and supervised by the author of the paper. After a short introduction and brief discussion of ANNs basic ideas, the activities in five areas are described: i) ANNs as a new independent computational tool for the analysis of C&SE problems, ii) neural networks in FEM/ ANN hybrid systems developed for the C&SE problems analysis, iii) various problems analyzed by ANNs, iv) modifications of BPNNs (Back-Propagation Neural Networks) and new learning methods, as well as other ANNs than those applied in problems mentioned above, v) promotion of ANNs. The representative six selected study cases are discussed: 1) concrete fatigue failure, 2) buckling of cylindrical shells with geometrical imperfections, 3) acceleration response spectra, 4) reliability of a plane frame, 5) hybrid updating of a thin-walled beam FE model, 6) hybrid identification of equivalent material in a perforated strip. Some general conclusions on prospects of ANNs applications in C&SE are given at the end of the paper.